The cranial morphology of the primitive anomodont genus Eodicynodon Barry, and its palaeoenvironment - Rubidge, Bruce Sidney (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1983.